Manufacturing method of rare earth magnet
By using a first coating with moderate zinc content and a second coating that prevents modification in the Sm-Fe-N rare earth magnet manufacturing process, combined with magnetic field forming and high temperature heat treatment, the problem of existing magnets-demagnetization in high temperature environments is solved, achieving higher magnetization and more efficient motor performance.
Patent Information
- Application Number
- JP2022032499
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-03
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-03-03
AI Technical Summary
The existing Sm-Fe-N rare earth magnet manufacturing method is easy to demagnetize in high temperature environments, and the magnetization degree is difficult to reach the expected value, which affects the efficiency and economy of the motor.
Using magnetic powder containing the first and second particle groups, a first coating with a zinc content of 3.0% to 10.0% is formed on the surface of the first particle group, and a second coating with a modification-proofing layer is formed on the surface of the second particle group, and a magnetic field forming and high temperature heat treatment are used to form a Fe-Zn alloy phase to improve coercivity.
The magnetic density and magnetization of rare earth magnets are improved, the -demagnetization risk in high-temperature environments is reduced, and the efficiency and economy of the motor are enhanced.
Smart Images

Figure 0007670638000003 
Figure 0007670638000004 
Figure 0007670638000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a rare earth magnet and a manufacturing method thereof. In particular, the present disclosure relates to a rare earth magnet containing Sm, Fe, and N, and at least a portion of which is Th2Zn 17 Type and Th2Ni 17 The present invention relates to a method for producing a rare earth magnet having a magnetic phase having any one of the crystal structures of the above types. [Background technology]
[0002] As high-performance rare earth magnets, Sm-Co rare earth magnets and Nd-Fe-B rare earth magnets have been put to practical use, but in recent years, rare earth magnets other than these have been under study.
[0003] For example, rare earth magnets containing Sm, Fe, and N (hereinafter sometimes referred to as "Sm-Fe-N rare earth magnets") have been considered. Sm-Fe-N rare earth magnets are manufactured using, for example, magnetic powder containing Sm, Fe, and N (hereinafter sometimes referred to as "SmFeN powder").
[0004] SmFeN powder is Th2Zn 17 Type and Th2Ni 17 It has a magnetic phase with either one of the crystal structures. This magnetic phase is thought to be a solid solution of N interstitially dissolved in the Sm-Fe crystal. Therefore, SmFeN powder is easily decomposed by N dissociation due to heat. For this reason, Sm-Fe-N rare earth magnets are often manufactured by molding SmFeN powder with resin and / or rubber.
[0005] Other methods for producing Sm-Fe-N rare earth magnets include, for example, the method disclosed in Patent Document 1. This method involves mixing SmFeN powder with powder containing metallic zinc (hereinafter sometimes referred to as "metallic zinc powder"), compacting the mixed powder in a magnetic field, and sintering (including liquid phase sintering) the magnetically compacted body.
[0006] Methods for producing SmFeN powder are disclosed in, for example, Patent Documents 2 and 3. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2015 / 199096 [Patent Document 2] JP 2017-117937 A [Patent Document 3] JP 2020-102606 A Summary of the Invention [Problem to be solved by the invention]
[0008] Methods for sintering magnetically compacted bodies are roughly divided into pressureless sintering and pressure sintering. In either sintering method, a high-density rare earth magnet (sintered body) can be obtained by sintering the magnetically compacted body. In the pressureless sintering method, since no pressure is applied to the magnetically compacted body during sintering, it is common to sinter the magnetically compacted body at a high temperature of 900°C or more for a long period of time of 6 hours or more to obtain a high-density sintered body. On the other hand, in the pressure sintering method, since pressure is applied to the magnetically compacted body during sintering, it is common to obtain a high-density sintered body even if the magnetically compacted body is sintered at a low temperature of 600 to 800°C for a short period of time of 0.1 to 5 hours.
[0009] When sintering a magnetic compact of a mixed powder of SmFeN powder and metal zinc powder, pressure sintering is adopted to avoid thermal decomposition of the SmFeN powder, but sintering is performed at a lower temperature and in a shorter time than the sintering temperature of normal pressure sintering. Sintering is possible at such a low temperature and in such a short time because the zinc component in the metal zinc powder diffuses to the surface of the magnetic powder during sintering and sinters (solidifies). In this way, the metal zinc powder in the magnetic compact functions as a binder. In addition, the metal zinc powder in the magnetic compact functions as a modifier, which modifies the α-Fe phase in the SmFeN powder and absorbs oxygen in the SmFeN powder to improve the coercive force. Hereinafter, the powder used in the production of Sm-Fe-N rare earth magnets and has both the function of a binder and the function of a modifier may be referred to as a "modifier powder".
[0010] In both cases where the magnetic powder is molded using resin and / or rubber, or where a mixed powder of the magnetic powder and modifier powder is pressure sintered, the magnetization of the molded body (rare earth magnet) decreases by the content ratio of the resin and modifier that do not contribute to magnetization. On the other hand, compared to the case where the magnetic powder is molded using resin and / or rubber, etc., when the mixed powder of the magnetic powder and modifier powder, or the coated magnetic powder, is pressure sintered, a high density molded body (rare earth magnet) is generally obtained, and as a result, it is easy to obtain high magnetization. However, when the magnetic powder is SmFeN powder, even if the mixed powder of the magnetic powder and modifier powder is pressure sintered, the magnetization is lower than expected from the content ratio of the modifier, and the desired magnetization cannot be obtained.
[0011] In addition, when permanent magnets such as Sm-Fe-N rare earth magnets are used in motors, the permanent magnets are placed in an external magnetic field environment that changes periodically. Therefore, the permanent magnets are affected by the external magnetic field. In an ideal permanent magnet, the magnetization does not decrease due to the external magnetic field in the motor's operating range, but in an actual permanent magnet, the magnetization decreases due to the external magnetic field in the motor's operating range. If the decrease in magnetization (demagnetization) due to the external magnetic field is large in the motor's operating range, the current control on the stator side of the motor becomes complicated and the load on the inverter connected to the motor increases. To reduce the load on the inverter, an inverter with a large capacity is required, which reduces the cost. This is particularly noticeable when the motor operates at high output and the permanent magnets inside the motor become hot.
[0012] In view of these circumstances, the inventors have discovered that there is a need for a method for manufacturing an Sm-Fe-N rare earth magnet that can achieve even greater magnetization than conventional magnets and that is less susceptible to demagnetization than conventional magnets in the motor operating range, particularly at high temperatures.
[0013] The present disclosure has been made to solve the above problems, and aims to provide a method for producing an Sm-Fe-N rare earth magnet that can further improve magnetization compared to conventional magnets and is less susceptible to demagnetization than conventional magnets, particularly at high temperatures, in an environment where an external magnetic field is applied. [Means for solving the problem]
[0014] The present inventors have conducted intensive research to achieve the above object, and have completed the method for producing a rare earth magnet according to the present disclosure. The method for producing a rare earth magnet according to the present disclosure includes the following aspects. <1> Contains Sm, Fe, and N, and is at least partially Th2Zn 17 Type and Th2Ni 17 A method for producing a rare earth magnet having a magnetic phase having any one of the crystal structures of the above types, comprising the steps of: Providing a magnetic powder comprising a first group of particles and a second group of particles; forming a first coating on the surfaces of the particles of the first particle group of the magnetic powder to obtain a first coated magnetic powder; forming a second coating on the surfaces of the particles of the second particle group of the magnetic powder to obtain a second coated magnetic powder; mixing the first coated magnetic powder and the second coated magnetic powder to obtain a mixed powder; The mixed powder is compression-molded in a magnetic field to obtain a magnetically molded body. Pressure sintering the magnetic field compact to obtain a sintered body; and heat treating the sintered body; Including, The particle size distribution D of the first particle group 50 is expressed in d1μm, and the particle size distribution D of the second particle group 50 is expressed in d2μm, The d1 and d2 satisfy the relationship of 0.350≦d2 / d1≦0.500, a ratio of a total volume of the first particle group to a total volume of the second particle group (total volume of the first particle group:total volume of the second particle group) is in the range of 9:1 to 4:1, The first coating contains zinc, and the content of the zinc component in the first coated magnetic powder is 3.0 mass% or more and 10.0 mass% or less with respect to the total mass of the first coated magnetic powder and the second coated magnetic powder, and During the heat treatment, the first coating advances the modification of the surfaces of the particles of the first particle group, and the second coating inhibits the surfaces of the particles of the second particle group from being modified by the adjacent first coating. A method for manufacturing rare earth magnets. <2> The method for producing a rare earth magnet according to <1>, wherein the second coating contains phosphoric acid. <3> The method for producing a rare earth magnet according to <1> or <2>, further comprising heat-treating the sintered body until an Fe-Zn alloy phase is formed on at least 75% of the surfaces of the particles of the first particle group. <4> The method for producing a rare earth magnet according to any one of <1> to <3>, wherein the heat treatment is carried out at a temperature of 350°C or higher and 410°C or lower. <5> The method for producing a rare earth magnet according to any one of <1> to <4>, wherein the heat treatment is carried out for 3 hours or more and 40 hours or less. <6> The method for producing a rare earth magnet according to any one of <1> to <5>, wherein the magnetically compacted body is pressure-sintered at a pressure of 200 MPa to 1500 MPa and a temperature of 300°C to 400°C for 1 minute to 30 minutes. Effect of the Invention
[0015] According to the present disclosure, the density of a sintered body (rare earth magnet) is improved by using a magnetic powder including a first particle group (large particle group) and a second particle group (small particle group), and during heat treatment of the sintered body, the modification of the surface of the particles of the first particle group is promoted and the modification of the surface of the particles of the second particle group is suppressed. As a result, it is possible to provide a method for producing a Sm-Fe-N rare earth magnet that is resistant to demagnetization, particularly at high temperatures, by improving the density of the sintered body, and controlling the modification between the first particle group and the second particle group and reducing the difference in coercivity between the first particle group and the second particle group. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic diagram showing an example of the structure of a rare earth magnet obtained by the manufacturing method of the present disclosure. [Diagram 2] FIG. 2 is a schematic diagram showing an example of the structure in a sintered body before heat treatment. [Diagram 3] FIG. 3 is a graph showing the demagnetization curve of a compact of low coercivity powder and that of a compact of a mixed powder of low coercivity powder and high coercivity powder at high temperatures. [Figure 4] FIG. 4 is an explanatory diagram showing an example of a method for forming a zinc-containing coating (first coating) on the surfaces of particles of SmFeN powder (first particle group) by using a rotary kiln. [Diagram 5] FIG. 5 is an explanatory diagram showing an example of a method for forming a coating (first coating) containing zinc on the surfaces of particles of SmFeN powder (first particle group) by a vapor deposition method. [Figure 6] FIG. 6 is a schematic diagram showing the structure of the samples of Comparative Examples 1 and 2. As shown in FIG. [Figure 7] FIG. 7 is a schematic diagram showing the structures of the samples of Comparative Examples 3 to 5. As shown in FIG. [Figure 8]FIG. 8 is a schematic diagram showing the structure of the sample of Comparative Example 7. [Figure 9] FIG. 9 is a schematic diagram showing the structure of the samples of Comparative Examples 8 and 9. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the manufacturing method for a rare earth magnet according to the present disclosure (hereinafter, sometimes referred to as the "manufacturing method according to the present disclosure") will be described in detail. Note that the manufacturing method according to the present disclosure is not limited to the embodiment described below.
[0018] Without being bound by theory, the reason why rare earth magnets obtained by the manufacturing method of the present disclosure have higher magnetization and are less susceptible to demagnetization, particularly at high temperatures, than rare earth magnets obtained by conventional manufacturing methods can be explained as follows, using the drawings.
[0019] Fig. 1 is a schematic diagram showing an example of the structure of a rare earth magnet obtained by the manufacturing method of the present disclosure. As shown in Fig. 1, a rare earth magnet 90 obtained by the manufacturing method of the present disclosure has SmFeN powder 10 including a first particle group 11 and a second particle group 12. A modifier phase 20 is formed on the surface of the particles of the first particle group 11. This modifier phase 20 bonds the particles of the first particle group 11 to each other, or bonds the particles of the first particle group 11 to the particles of the second particle group 12, to form the rare earth magnet 90.
[0020] In the rare earth magnet 90 obtained by the manufacturing method of the present disclosure, the particles of the second particle group 12 having a small particle size are present between the particles of the first particle group 11 having a large particle size. This improves the density of the rare earth magnet 90, and as a result, improves the magnetization of the rare earth magnet 90. Here, to improve the density, it is necessary that the ratio of the particle size of the second particle group 12 to the particle size of the first particle group 11 is within a predetermined range, and that the ratio of the total volume of the first particle group 11 to the total volume of the second particle group 12 is within a predetermined range.
[0021] As described above, each particle of the SmFeN powder 10 is bonded by the modified phase 20 on the particle surface of the first particle group 11. The modified phase 20 on the particle surface of the first particle group 11 originates from the first coating formed on the particle surface of the first particle group 11 before pressure sintering. The formation of the modified phase 20 will be described with reference to the drawings.
[0022] 2 is a schematic diagram showing an example of the structure in a sintered body before heat treatment. A first coated magnetic powder 31 and a second coated magnetic powder 32 are present in a sintered body 30 before heat treatment. In the first coated magnetic powder 31, a first coating 41 is present on the surfaces of the particles of the first particle group 11. In the second coated magnetic powder 32, a second coating 42 is present on the surfaces of the particles of the second particle group 12.
[0023] Since the first coating 41 contains zinc, Fe diffuses from the particle surfaces of the first particle group 11 into the first coating 41 during heat treatment of the sintered body 30. Then, this Fe is alloyed with the Zn in the first coating 41 to form an Fe-Zn alloy phase in the first coating 41. This Fe-Zn phase is the modified phase 20. The Fe that diffuses into the first coating 41 is mainly derived from the α-Fe phase that is present on the particle surfaces of the first particle group 11. The α-Fe phase is SmFeN powder and Th2Zn 17 Type and Th2Ni 17 The α-Fe phase is composed of Fe that did not contribute to the formation of a magnetic phase having any of the crystal structures of the α-Fe type. The α-Fe phase is a soft magnetic phase, which causes a decrease in coercivity. Therefore, by modifying the α-Fe phase to obtain a nonmagnetic modified phase 20 (Fe-Zn phase), the coercivity is improved.
[0024] On the other hand, the second coating 42 suppresses the formation of a nonmagnetic modified phase (Fe-Zn phase) on the particle surfaces of the second particle group 12 due to Zn diffusing from the adjacent first coating 41 on the Fe on the particle surfaces of the second particle group 12 during heat treatment of the sintered body 30. That is, the second coating 42 suppresses the particle surfaces of the second particle group 12 from being modified by the first coating 41. The second coating 42 contains a substance that suppresses the modification of the particle surfaces of the second particle group 12, and such a substance will be described later. In the manufacturing method of the present disclosure, the particle surfaces of the first particle group 11 are modified, but the modification of the particle surfaces of the second particle group 12 is suppressed for the following reasons.
[0025] When magnetic powder contains magnetic powder having high coercivity (hereinafter sometimes referred to as "high coercivity powder") and magnetic powder having low coercivity (hereinafter sometimes referred to as "low coercivity powder"), the squareness of a compact of such magnetic powder, particularly at high temperatures, may decrease. This can be explained as follows using the drawings. In this specification, unless otherwise specified, "high temperature" in relation to magnetic properties means 100 to 200°C, and squareness is measured at a temperature of 10% demagnetization H k Evaluate based on:
[0026] 3 is a graph showing the demagnetization curves of a compact of low coercivity powder and a compact of a mixed powder of low coercivity powder and high coercivity powder at high temperatures. It can be seen from Fig. 3 that the compact of low coercivity powder is inferior in coercivity to the compact of the mixed powder of low coercivity powder and high coercivity powder, but is superior in squareness.
[0027] In the SmFeN magnetic powder, a magnetic powder having a large particle size has a low coercive force, and a magnetic powder having a small particle size has a high coercive force. In the magnetic powder used in the manufacturing method of the present disclosure, the first particle group corresponds to the low coercive force powder, and the second particle group corresponds to the high coercive force powder.
[0028] As shown in FIG. 2, in the sintered body 30 before the heat treatment, the first particle group 11 has a first coating 41 on the particle surface, and the second particle group 12 has a second coating 42 on the particle surface. By heat treating such a sintered body 30, as described above, the first particle group 11 is modified and the coercive force is improved, and the second particle group 12 is suppressed from being modified by the second coating 42 and the increase in the coercive force is suppressed. As a result, in the sintered body 30 after the heat treatment, the difference between the coercive force of the first particle group 11 and the coercive force of the second particle group 12 can be suppressed from increasing, and the squareness can be improved. As a result, the density of the sintered body is improved between the first particle group and the second particle group, and even if the magnetization is improved, the squareness, especially the squareness at high temperatures, is improved. If the squareness is improved, demagnetization is less likely to occur in an environment where an external magnetic field is applied.
[0029] For these reasons, the rare earth magnet 90 (sintered body 30 after heat treatment) obtained by the manufacturing method of the present disclosure has a structure in which the modified phase 20 is formed on the particle surfaces of the first particle group 11, but the modified phase 20 is not substantially formed on the particle surfaces of the second particle group 12. Furthermore, in the example of FIG. 1, in the rare earth magnet 90 (sintered body 30 after heat treatment) obtained by the manufacturing method of the present disclosure, substantially no coating is observed on the particle surfaces of the second particle group 12. This is believed to be because the second coating 42 present in the sintered body 30 before heat treatment, when it fulfills its function of suppressing modification during heat treatment, typically decomposes into the elements constituting the second coating 42, and the elements are dispersed on the modified phase 20 or the particle surfaces of the second particle group 12, but is not limited to this, and part or all of the second coating 42 may remain on the rare earth magnet 90 (sintered body 30 after heat treatment).
[0030] The constituent elements of the manufacturing method of the present disclosure, which has been completed based on the findings and the like described thus far, will now be described.
[0031] <<Manufacturing method of rare earth magnets>> The manufacturing method of the present disclosure includes a magnetic powder preparation step, a first coated magnetic powder preparation step, a second coated magnetic powder preparation step, a mixing step, a magnetic field compaction step, a pressure sintering step, and a heat treatment step. Each step will be described below.
[0032] <Magnetic powder preparation process> A magnetic powder (SmFeN powder) is prepared. The magnetic powder (SmFeN powder) used in the manufacturing method of the present disclosure contains Sm, Fe, and N, and at least a portion of the SmFeN powder is SmFeN powder. 17 Type and Th2Ni 17 There are no particular limitations as long as the magnetic phase has a crystal structure of any of the above types. In addition to the above-mentioned structures, the crystal structure of the magnetic phase may be a phase having a TbCu7 type crystal structure. Sm is samarium, Fe is iron, and N is nitrogen. Th is thorium, Zn is zinc, Ni is nickel, Tb is terbium, and Cu is copper.
[0033] In the SmFeN powder, for example, the composition formula (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N h The rare earth magnet obtained by the manufacturing method of the present disclosure (hereinafter, sometimes referred to as the "result") exhibits magnetization due to the magnetic phase in the SmFeN powder. Here, i, j, and h are molar ratios.
[0034] The magnetic phase in the SmFeN powder may contain R within a range that does not impair the effect of the manufacturing method of the present disclosure and the magnetic properties of the product. The range of R is represented by i in the above composition formula. i may be, for example, 0 or more, 0.10 or more, or 0.20 or more, and may be 0.50 or less, 0.40 or less, or 0.30 or less. R is one or more elements selected from rare earth elements other than Sm and Zr. In this specification, the rare earth elements are Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. In addition, Zr is zirconium, Sc is scandium, Y is yttrium, La is lanthanum, Ce is cerium, Pr is praseodymium, Nd is neodymium, Pm is promethium, Sm is samarium, Eu is europium, Gd is gadolinium, Tb is terbium, Dy is dysprosium, Ho is holmium, Er is erbium, Tm is thulium, Yb is ytterbium, and Lu is lutetium.
[0035] (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N h For example, Sm2(Fe (1-j) Co j ) 17 N h The Sm position is substituted with R, but this is not limited to this. For example, Sm2(Fe (1-j) Co j ) 17 N h A part of R may be interstitially arranged in the
[0036] The magnetic phase in the SmFeN powder may contain Co within a range that does not impair the effects of the manufacturing method of the present disclosure and the magnetic properties of the product. Such a range is represented by j in the above composition formula. j may be 0 or more, 0.10 or more, or 0.20 or more, and may be 0.52 or less, 0.40 or less, or 0.30 or less.
[0037] (Sm (1-i) R i )2(Fe(1-j) Co j ) 17 N h Typically, for (Sm (1-i) R i )2Fe 17 N h Co is substituted for the Fe position in, but this is not limited to this. For example, (Sm (1-i) R i )2Fe 17 N h A part of Co may be interstitially arranged in the GaN layer.
[0038] The magnetic phase in the SmFeN powder is (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 The presence of interstitial N in the crystal grains represented by the formula (I) contributes to the development and improvement of magnetic properties.
[0039] (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N h For h, h can be 1.5 to 4.5, but typically, (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N3. h may be 1.8 or more, 2.0 or more, or 2.5 or more, and may be 4.2 or less, 4.0 or less, or 3.5 or less. (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N h For the whole (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 The content of N3 is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more. (1-i) R i )2(Fe (1-j) Coj ) 17 N h All of this (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 It doesn't have to be N3. (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N h For the whole (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 The content of N3 may be 98% by mass or less, 95% by mass or less, or 92% by mass or less.
[0040] SmFeN powder is (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N h In addition to the magnetic phase represented by the formula (I), oxygen and M may be added to the range that does not substantially impair the effect of the manufacturing method of the present disclosure and the magnetic properties of the product. 1 In order to ensure the magnetic properties of the resulting product, the total amount of SmFeN powder (Sm (1-i) R i )2(Fe (1-j) Co j ) 17 N h The content of the magnetic phase represented by may be 80 mass% or more, 85 mass% or more, or 90 mass% or more. (1-i) R i )2(Fe (1-j) Co j ) 17 N h There is no practical problem even if the content of the magnetic phase represented by the formula (Sm) is not excessively high. Therefore, the content may be 97% by mass or less, 95% by mass or less, or 93% by mass or less. (1-i) R i )2(Fe (1-j) Co j ) 17N h The remainder of the magnetic phase represented by is oxygen and M 1 content. Also, a part of oxygen and M 1 may be present in the magnetic phase in an interstitial and / or substitutional form.
[0041] The above-mentioned M 1 includes one or more elements selected from Ga, Ti, Cr, Zn, Mn, V, Mo, W, Si, Re, Cu, Al, Ca, B, Ni, and C. Inescapable impurity elements refer to impurity elements that cannot be avoided during the production of raw materials and / or magnetic powder, or that would cause a significant increase in production costs to avoid. These elements may be present in the above-mentioned magnetic phase in a substitutional and / or interstitial form, or may be present in a phase other than the above-mentioned magnetic phase. Alternatively, they may be present at the grain boundaries of these phases. Note that Ga is gallium, Ti is titanium, Cr is chromium, Zn is zinc, Mn is manganese, V is vanadium, Mo is molybdenum, W is tungsten, Si is silicon, Re is rhenium, Cu is copper, Al is aluminum, Ca is calcium, B is boron, Ni is nickel, and C is carbon.
[0042] The SmFeN powder includes a first particle group and a second particle group. The particles of the first particle group have a large particle size, and the particles of the second particle group have a small particle size. The particle sizes of the particles in each of the first particle group and the second particle group can be represented by the particle size distribution D 50 The particle size distribution D of the first particle group 50 is represented by d1 μm, and the particle size distribution D of the second particle group 50 is represented by d2 μm. And d1 and d2 satisfy the relationship 0.350 ≦ d2 / d1 ≦ 0.500. From satisfying the above relationship, it is clear that d2 < d1, that is, the first particle group has a large particle size and the second particle group has a small particle size.
[0043] When d2 / d1 is 0.350 or more, 0.360 or more, 0.370 or more, or 0.378 or more, and 0.500 or less, 0.490 or less, 0.486 or less, 0.480 or less, 0.470 or less, or 0.467 or less, the particles of the second particle group are advantageously present between the particles of the first particle group, increasing the density of the molded body (rare earth magnet) and, as a result, improving magnetization.
[0044] As long as the above relationship is satisfied, the particle size of each of the first particle group and the second particle group is not particularly limited, but in order to easily satisfy the above relationship, it is preferable that d1 and d2 are each independently within the following ranges. d1 is preferably 3.0 μm or more, 3.2 μm or more, or 3.4 μm or more, and is preferably 3.7 μm or less, 3.6 μm or less, or 3.5 μm or less. d2 is preferably 1.4 μm or more or 1.5 μm or more, and is preferably 1.8 μm or less, 1.7 μm or less, or 1.6 μm or less.
[0045] The ratio of the total volume of the first particle group to the total volume of the second particle group, i.e., (total volume of the first particle group):(total volume of the second particle group), must be in the range of 9:1 to 4:1. (Total volume of the first particle group):(Total volume of the second particle group) being 9:1 means, for example, that the total volume of the first particle group is 90% and the total volume of the second particle group is 10% of the total volume of the SmFeN powder. Also, (Total volume of the first particle group):(Total volume of the second particle group) being 4:1 means, for example, that the total volume of the first particle group is 80% and the total volume of the second particle group is 20% of the total volume of the SmFeN powder.
[0046] If the ratio of (total volume of the first particle group):(total volume of the second particle group) is 9:1 or the total volume of the second particle group is greater than that, the particles of the second particle group are advantageously present between the particles of the first particle group, increasing the density of the rare earth magnet and, as a result, improving magnetization. From this perspective, the ratio of (total volume of the first particle group):(total volume of the second particle group) is preferably 8.8:1.2 or more or 8.6:1.4 or more.
[0047] If there is an excess of particles of the second particle group, the gaps between the particles of the first particle group will be warped and enlarged. To avoid this, the ratio of (total volume of the first particle group):(total volume of the second particle group) must be 4:1 or the total volume of the second particle group must be less than that. In addition, the small particle size of SmFeN powder particles such as the second particle group has a particle remanent magnetization σ r Therefore, if the second particle group is present in excess, it will lead to a decrease in the magnetization of the entire rare earth magnet. For this reason, it is necessary to prevent the spacing between the first particle group from increasing, thereby suppressing a decrease in the density of the rare earth magnet and reducing σ r By reducing the number of the second particle group having a small particle size, the magnetization of the rare earth magnet is improved. From these viewpoints, the ratio of (total volume of the first particle group):(total volume of the second particle group) is preferably 8.2:1.8 or less or 8.4:1.6 or less.
[0048] The magnetic powder containing the first particle group and the second particle group is typically obtained by classifying the SmFeN powder obtained by the manufacturing method described below into the first particle group and the second particle group. There is no particular limitation on the classification method, and any known method may be used. Examples of the classification method include sieve classification and air classification, and these may be combined.
[0049] SmFeN powder D 50 is calculated from the particle size distribution of the SmFeN powder, which is measured (investigated) by the following method. In this specification, unless otherwise specified, the description of the particle size (particle size) of the SmFeN powder is based on the following measurement method (investigation method). 50 means the median diameter.
[0050] A sample was prepared by embedding SmFeN powder in resin, and the surface of the sample was polished and observed under an optical microscope. A straight line was then drawn on the optical microscope image, and the length of the line segment where the line was divided by SmFeN particles (bright field) was measured, and the particle size distribution of the SmFeN powder was calculated from the frequency distribution of the line segment length. The particle size distribution calculated by this method is almost equal to the particle size distribution calculated by the intersection method or the dry laser diffraction / scattering method.
[0051] Although fine particles may be present in the SmFeN powder for reasons of manufacturing convenience, etc., as long as d1 and d2 satisfy the above-mentioned relationship, there is no particular restriction on the ratio of magnetic particles (fine particles) having a particle size of 1.0 μm or less in the SmFeN powder. The ratio of magnetic particles (fine particles) having a particle size of 1.0 μm or less in the SmFeN powder is preferably as low as possible from the viewpoint of ensuring the mechanical strength of the compact (rare earth magnet). The ratio of fine particles to the total number of magnetic particles in the SmFeN powder is preferably 10.0% or less, 8.0% or less, 6.0% or less, or 4.0% or less. From the viewpoint of manufacturing convenience of the SmFeN powder, fine particles do not have to be completely absent, and there is no practical problem even if the lower limit of the ratio of fine particles is 1.0%, 2.0%, or 3.0%. Even if fine particles are present, the fine Fe-Zn alloy phase derived from the fine particles is generally not observed by heat treating the sintered body. The reason is considered to be as follows. In the fine particles of SmFeN powder, an Fe-Zn alloy phase is formed not only on the particle surface but also throughout the particle during heat treatment of the sintered body. This is because in the fine particles, the Fe-Zn alloy phase is formed in the form of Th2Zn 17 Type and / or Th2Ni 17 This is because the proportion of parts in which the crystal structure of the first particle group is not perfect is large. Furthermore, most of the Fe-Zn alloy phase derived from the fine powder particles is integrated with the modified phase (Fe-Zn alloy phase) formed on the particle surfaces of the first particle group.
[0052] Oxygen in the SmFeN powder causes a decrease in coercivity. The decrease in coercivity is often a problem with magnetic powders having large particle sizes. In the manufacturing method disclosed herein, the first particle group (magnetic powders having large particle sizes) is modified. During the modification, the zinc in the first coating absorbs oxygen, thereby suppressing the decrease in coercivity. The oxygen content in the SmFeN powder may be determined in consideration of the amount of oxygen absorbed by the zinc in the first coating in the SmFeN powder. The oxygen content of the SmFeN powder is preferably low relative to the entire SmFeN powder. The oxygen content of the SmFeN powder is preferably 2.0 mass% or less, more preferably 1.5 mass% or less, and even more preferably 1.0 mass% or less relative to the entire SmFeN powder. On the other hand, excessive reduction in the oxygen content in the SmFeN powder leads to an increase in manufacturing costs. Therefore, the oxygen content of the SmFeN powder may be 0.1 mass % or more, 0.2 mass % or more, or 0.3 mass % or more, based on the entire SmFeN powder.
[0053] As long as the SmFeN powder satisfies the above description, there is no particular limitation on the manufacturing method thereof, and a commercially available product may be used. Examples of the manufacturing method of the SmFeN powder include a method in which Sm-Fe powder is manufactured from samarium oxide and iron powder by a reduction diffusion method, and the Sm-Fe powder is heated at 600°C or less in an atmosphere of a mixed gas of nitrogen and hydrogen, nitrogen gas, ammonia gas, or the like to obtain Sm-Fe-N powder. Alternatively, examples of the manufacturing method include a method in which an Sm-Fe alloy is manufactured by a melting method, the alloy is coarsely crushed to obtain coarsely crushed particles, which are then nitrided and further crushed to a desired particle size. For the crushing, for example, a dry jet mill, a dry ball mill, a wet ball mill, or a wet bead mill can be used. These may be used in combination.
[0054] In addition to the above-mentioned manufacturing method, the SmFeN powder can be obtained by a manufacturing method including a pretreatment step of heat-treating an oxide containing Sm and Fe in a reducing gas-containing atmosphere to obtain a partial oxide, a reduction step of heat-treating the partial oxide in the presence of a reducing agent to obtain alloy particles, and a nitriding step of heat-treating the alloy particles in a nitrogen or ammonia-containing atmosphere at a first temperature of 400° C. to 470° C., and then at a second temperature of 480° C. to 610° C. to obtain nitrides. In particular, in alloy particles having a large particle size, such as alloy particles containing La, nitridation may not progress sufficiently to the inside of the oxide particles, but when nitriding is performed at two temperatures, the inside of the oxide particles is also sufficiently nitrided, and anisotropic SmFeN powder with a narrow particle size distribution and high remanent magnetization can be obtained.
[0055] [Oxide preparation process] The oxide containing Sm and Fe used in the pretreatment step described below may be prepared, for example, by mixing Sm oxide and Fe oxide. However, it is preferable to produce the oxide containing Sm and Fe by a process including mixing a solution containing Sm and Fe with a precipitant to obtain a precipitate containing Sm and Fe (precipitation process) and firing the precipitate to obtain an oxide containing Sm and Fe (oxidation process).
[0056] [Precipitation process] In the precipitation process, the Sm and Fe raw materials are dissolved in a strongly acidic solution to prepare a solution containing Sm and Fe. 17 When N3 is obtained as the main phase, the molar ratio of Sm and Fe (Sm:Fe) is preferably 1.5:17 to 3.0:17, more preferably 2.0:17 to 2.5:17. Raw materials such as La, W, Co, Ti, Sc, Y, Pr, Nd, Pm, Gd, Tb, Dy, Ho, Er, Tm, and / or Lu may be added to the above-mentioned solution. In terms of residual magnetic flux density, it is preferable to contain La. In terms of coercive force and squareness ratio, it is preferable to contain W. In terms of temperature characteristics, it is preferable to contain Co and / or Ti.
[0057] The Sm raw material and the Fe raw material are not limited as long as they can be dissolved in a strong acidic solution. For example, in terms of ease of availability, the Sm raw material may be samarium oxide, and the Fe raw material may be FeSO4. The concentration of the solution containing Sm and Fe may be appropriately adjusted within a range in which the Sm raw material and the Fe raw material are substantially dissolved in the acidic solution. In terms of solubility, the acidic solution may be sulfuric acid.
[0058] By reacting the solution containing Sm and Fe with a precipitant, an insoluble precipitate containing Sm and Fe is obtained. Here, the solution containing Sm and Fe may be a solution containing Sm and Fe when reacted with the precipitant. For example, raw materials containing Sm and Fe may be prepared as separate solutions, and each solution may be dropped to react with the precipitant. Even when preparing them as separate solutions, each raw material is appropriately adjusted to a range in which it is substantially soluble in the acidic solution. The precipitant is not limited as long as it is an alkaline solution that reacts with the solution containing Sm and Fe to obtain a precipitate, and examples of the precipitant include ammonia water and caustic soda, with caustic soda being preferred.
[0059] The precipitation reaction is preferably carried out by dropping a solution containing Sm and Fe and a precipitant into a solvent such as water, from the viewpoint of easily adjusting the properties of the particles of the precipitate. By appropriately controlling the supply rate of the solution containing Sm and Fe and the precipitant, the reaction temperature, the concentration of the reaction solution, the pH during the reaction, etc., a precipitate having a uniform distribution of the constituent elements, a narrow particle size distribution, and a regular powder shape can be obtained. By using such a precipitate, the magnetic properties of the final product, SmFeN powder, are improved. The reaction temperature can be set to 0°C or higher and 50°C or lower, and preferably 35°C or higher and 45°C or lower. The concentration of the reaction solution is preferably 0.65 mol / L or higher and 0.85 mol / L or lower, and more preferably 0.7 mol / L or higher and 0.85 mol / L or lower, as the total concentration of metal ions. The reaction pH is preferably 5 to 9, and more preferably 6.5 to 8.
[0060] The solution containing Sm and Fe preferably further contains one or more metals selected from the group consisting of La, W, Co, and Ti in terms of magnetic properties. For example, it is preferable to contain La in terms of residual magnetic flux density, it is preferable to contain W in terms of coercive force and squareness ratio, and it is preferable to contain Co and / or Ti in terms of temperature properties. The La raw material is not limited as long as it can be dissolved in a strongly acidic solution, and examples of the La raw material include La2O3 and LaCl3 in terms of ease of availability. The La raw material, W raw material, Co raw material, and Ti raw material are appropriately adjusted to a range in which they are substantially dissolved in the acidic solution together with the Sm raw material and the Fe raw material, and sulfuric acid is used as the acidic solution in terms of solubility. The W raw material includes ammonium tungstate, the Co raw material includes cobalt sulfate, and the titanium raw material includes titania sulfate.
[0061] When the solution containing Sm and Fe further contains one or more metals selected from the group consisting of La, W, Co, and Ti, an insoluble precipitate containing Sm, Fe, and one or more selected from the group consisting of La, W, Co, and Ti is obtained. Here, the solution only needs to contain one or more selected from the group consisting of La, W, Co, and Ti when reacting with the precipitant, and for example, each raw material may be prepared as a separate solution and each solution may be dropped to react with the precipitant, or may be prepared together with the solution containing Sm and Fe.
[0062] The powder obtained in the precipitation process determines the powder particle size, powder shape, and particle size distribution of the final SmFeN powder. When the particle size of the obtained powder is measured by a laser diffraction type wet particle size distribution meter, it is preferable that the size and distribution of the entire powder is approximately in the range of 0.05 μm to 20 μm, preferably 0.1 μm to 10 μm.
[0063] After separating the precipitate, it is preferable to remove the solvent from the separated material in order to prevent the precipitate from redissolving in the remaining solvent in the heat treatment of the subsequent oxidation step, causing aggregation of the precipitate when the solvent evaporates, or changes in particle size distribution, powder particle size, etc. Specific examples of the method for removing the solvent include a method in which, when water is used as the solvent, the precipitate is dried in an oven at 70°C to 200°C for 5 hours to 12 hours.
[0064] After the precipitation step, a step of separating and washing the resulting precipitate may be included. The washing step is carried out so that the conductivity of the supernatant solution is 5 mS / m 2 The process is appropriately continued until the following is reached: In the step of separating the precipitate, for example, a solvent (preferably water) can be added to the obtained precipitate and mixed, followed by filtration, decantation, or the like.
[0065] [Oxidation process] The oxidation step is a step of obtaining an oxide containing Sm and Fe by firing the precipitate formed in the precipitation step. For example, the precipitate can be converted into an oxide by heat treatment. When the precipitate is heat treated, it must be performed in the presence of oxygen, and can be performed in an air atmosphere, for example. In addition, since it must be performed in the presence of oxygen, it is preferable that the nonmetallic part in the precipitate contains oxygen atoms.
[0066] The heat treatment temperature in the oxidation step (hereinafter sometimes referred to as "oxidation temperature") is not particularly limited, but is preferably 700°C or more and 1300°C or less, and more preferably 900°C or more and 1200°C or less. If the temperature is less than 700°C, the oxidation is insufficient, and if the temperature exceeds 1300°C, the desired shape, average particle size, and particle size distribution of the SmFeN powder tend not to be obtained. The heat treatment time is also not particularly limited, but is preferably 1 hour or more and 3 hours or less.
[0067] The oxide particles obtained are oxide particles in which Sm and Fe are thoroughly mixed microscopically and which reflect the shape, particle size distribution, etc. of the precipitate.
[0068] [Pretreatment process] The pretreatment step is a step in which the above-mentioned oxide containing Sm and Fe is heat-treated in an atmosphere containing a reducing gas to obtain a partial oxide in which a part of the oxide is reduced.
[0069] Here, the partial oxide refers to an oxide in which a part of an oxide is reduced. The oxygen concentration of the partial oxide is not particularly limited, but is preferably 10% by mass or less, and more preferably 8% by mass or less. If it exceeds 10% by mass, the reduction heat generated by Ca in the reduction step increases, and the firing temperature increases, which tends to result in particles that have undergone abnormal particle growth. Here, the oxygen concentration of the partial oxide can be measured by non-dispersive infrared absorption (ND-IR).
[0070] The reducing gas is appropriately selected from hydrocarbon gases such as hydrogen (H2), carbon monoxide (CO), and methane (CH4), but hydrogen gas is preferable from the viewpoint of cost, and the flow rate of the gas is appropriately adjusted within a range in which the oxide does not scatter. The heat treatment temperature in the pretreatment step (hereinafter, pretreatment temperature) is preferably 300°C or more and 950°C or less, and the lower limit is more preferably 400°C or more, and even more preferably 750°C or more. The upper limit is more preferably less than 900°C. When the pretreatment temperature is 300°C or more, the reduction of the oxide containing Sm and Fe proceeds efficiently. Furthermore, when the pretreatment temperature is 950°C or less, the particle growth and segregation of the oxide particles are suppressed, and the desired particle size can be maintained. The heat treatment time is not particularly limited, but can be 1 hour or more and 50 hours or less. Furthermore, when hydrogen is used as the reducing gas, it is preferable to adjust the thickness of the oxide layer used to 20 mm or less, and further adjust the dew point in the reaction furnace to -10°C or less.
[0071] [Reduction process] The reduction step is a step of obtaining alloy particles by heat treating the partial oxide in the presence of a reducing agent, for example, by contacting the partial oxide with calcium melt or calcium vapor. From the viewpoint of magnetic properties, the heat treatment temperature is preferably 920°C or more and 1200°C or less, more preferably 950°C or more and 1150°C or less, and even more preferably 980°C or more and 1100°C or less.
[0072] Metallic calcium, which is a reducing agent, is used in the form of granules or powder, and the particle size is preferably 10 mm or less. This makes it possible to more effectively suppress aggregation during the reduction reaction. Metallic calcium is preferably added in an amount of 1.1 to 3.0 times the reaction equivalent (the stoichiometric amount required to reduce the rare earth oxide, and if the Fe component is in the form of an oxide, includes the amount required to reduce it), and more preferably in an amount of 1.5 to 2.5 times.
[0073] In the reduction step, a disintegration promoter can be used as necessary together with the reducing agent, metallic calcium. The disintegration promoter is used as appropriate to promote disintegration and granulation of the product in the post-treatment step described below, and examples thereof include alkaline earth metal salts such as calcium chloride, and alkaline earth oxides such as calcium oxide. These disintegration promoters are used in a ratio of 1% by mass to 30% by mass, preferably 5% by mass to 30% by mass, based on the samarium oxide.
[0074] [Nitriding process] The nitriding step is a step of obtaining anisotropic magnetic particles by heat-treating the alloy particles obtained in the reduction step in a nitrogen or ammonia-containing atmosphere at a first temperature of 400°C to 470°C, and then heat-treating them at a second temperature of 480°C to 610°C to obtain anisotropic magnetic particles. Since the particulate precipitate obtained in the precipitation step is used, the alloy particles in the form of porous aggregates are obtained in the reduction step. This allows the alloy particles to be heat-treated and nitrided immediately in a nitrogen atmosphere without pulverization, so that the nitriding can be performed uniformly. If the alloy particles are heat-treated at a high second temperature without nitriding at the first temperature, the nitriding process will proceed rapidly, causing abnormal heat generation, which may cause SmFeN to decompose and greatly reduce the magnetic properties. In addition, the atmosphere in the nitriding step is preferably a substantially nitrogen-containing atmosphere, since the nitriding process can slow down the progress of nitriding. The term "substantially" used here is used in consideration of the fact that elements other than nitrogen are inevitably included due to the inclusion of impurities, etc., and for example, the ratio of nitrogen in the atmosphere is 95% or more, preferably 97% or more, and more preferably 99% or more.
[0075] The first temperature in the nitriding step is 400°C or more and 470°C or less, but preferably 410°C or more and 450°C or less. If it is less than 400°C, the nitriding proceeds very slowly, and if it exceeds 470°C, over-nitriding or decomposition is likely to occur due to heat generation. The heat treatment time at the first temperature is not particularly limited, but is preferably 1 hour or more and 40 hours or less, and more preferably 20 hours or less. If it is less than 1 hour, the nitriding may not proceed sufficiently, and if it exceeds 40 hours, the productivity decreases.
[0076] The second temperature is 480°C or more and 610°C or less, but preferably 500°C or more and 550°C or less. If the temperature is less than 480°C, nitriding may not proceed sufficiently if the particles are large, and if the temperature exceeds 610°C, over-nitriding or decomposition is likely to occur. The heat treatment time at the second temperature is preferably 15 minutes to 5 hours, and more preferably 30 minutes to 2 hours. If the temperature is less than 15 minutes, nitriding may not proceed sufficiently, and if the temperature exceeds 5 hours, productivity decreases.
[0077] The heat treatment at the first temperature and the heat treatment at the second temperature may be carried out continuously, and a heat treatment at a temperature lower than the second temperature may be included between these heat treatments. However, from the viewpoint of productivity, it is preferable to carry out the heat treatments continuously.
[0078] [Post-processing process] The product obtained after the nitriding step contains, in addition to the magnetic particles, by-produced CaO, unreacted metallic calcium, etc., and these may be in the form of a composite sintered lump. The product obtained after the nitriding step can be put into cooling water to separate the CaO and metallic calcium as a calcium hydroxide (Ca(OH)2) suspension. The remaining calcium hydroxide may be sufficiently removed by washing the magnetic powder with acetic acid, etc. When the product is put into water, the oxidation of metallic calcium by water and the hydration reaction of the by-produced CaO cause the composite sintered lump-like reaction product to disintegrate, i.e., to become fine powder.
[0079] [Alkaline treatment process] The product obtained after the nitriding step may be put into an alkaline solution. Examples of the alkaline solution used in the alkaline treatment step include an aqueous calcium hydroxide solution, an aqueous sodium hydroxide solution, and an aqueous ammonia solution. Among these, an aqueous calcium hydroxide solution and an aqueous sodium hydroxide solution are preferred in terms of wastewater treatment and high pH. The alkaline treatment of the product leaves an Sm-rich layer containing a certain amount of oxygen, which functions as a protective layer, thereby suppressing an increase in oxygen concentration due to the alkaline treatment.
[0080] The pH of the alkaline solution used in the alkaline treatment step is not particularly limited, but is preferably at least 9, and more preferably at least 10. If the pH is less than 9, the reaction rate when calcium hydroxide is produced is high and heat generation is large, so that the oxygen concentration in the finally obtained SmFeN powder tends to be high.
[0081] In the alkali treatment step, the moisture content of the SmFeN powder obtained after treatment with the alkaline solution can be reduced by a method such as decantation, if necessary.
[0082] [Acid treatment process] The alkaline treatment step may be followed by an acid treatment step in which the SmFeN powder is treated with an acid. In the acid treatment step, at least a part of the Sm-rich layer is removed to reduce the oxygen concentration in the entire SmFeN powder. In addition, in the manufacturing method according to the embodiment of the present invention, since no pulverization or the like is performed, the average particle size of the SmFeN powder is small, the particle size distribution is narrow, and no fine powder generated by pulverization or the like is included, so that it is possible to suppress an increase in the oxygen concentration.
[0083] The acid used in the acid treatment step is not particularly limited, and examples thereof include hydrogen chloride, nitric acid, sulfuric acid, acetic acid, etc. Among these, hydrogen chloride and nitric acid are preferred since they do not leave impurities behind.
[0084] The amount of acid used in the acid treatment step is preferably 3.5 parts by mass or more and 13.5 parts by mass or less, more preferably 4 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of SmFeN powder. If it is less than 3.5 parts by mass, oxides remain on the surface of the SmFeN powder, and the oxygen concentration becomes high. If it exceeds 13.5 parts by mass, reoxidation is likely to occur when exposed to the atmosphere, and the SmFeN powder is dissolved, so the cost tends to be high. By setting the amount of acid to 3.5 parts by mass or more and 13.5 parts by mass or less relative to 100 parts by mass of SmFeN powder, it is possible to make the Sm-rich layer oxidized to such an extent that reoxidation is unlikely to occur when exposed to the atmosphere after the acid treatment cover the surface of the SmFeN powder, so that SmFeN powder with a low oxygen concentration, a small average particle size, and a narrow particle size distribution can be obtained.
[0085] In the acid treatment step, the moisture content of the SmFeN powder obtained after the acid treatment can be reduced by a method such as decantation, if necessary.
[0086] [Dehydration process] It is preferable to include a dehydration step after the acid treatment step. The dehydration step reduces the moisture content in the solid content before vacuum drying, and suppresses the progress of oxidation during drying that occurs when the solid content before vacuum drying contains more moisture. Here, the dehydration step means a process in which pressure or centrifugal force is applied to reduce the moisture content of the solid content after treatment compared to the solid content before treatment, and does not include simple decantation, filtration, or drying. The dehydration method is not particularly limited, but examples include squeezing, centrifugation, and the like.
[0087] The amount of moisture contained in the SmFeN powder after the dehydration treatment is not particularly limited, but is preferably 13% by mass or less, and more preferably 10% by mass or less, in order to inhibit the progress of oxidation.
[0088] The SmFeN powder obtained by the acid treatment, or the SmFeN powder obtained by the acid treatment and then the dehydration treatment, is preferably vacuum dried. The drying temperature is not particularly limited, but is preferably 70° C. or higher, and more preferably 75° C. or higher. The drying time is also not particularly limited, but is preferably 1 hour or more, and more preferably 3 hours or more.
[0089] <First coated magnetic powder preparation process> A first coating is formed on the particle surface of a first particle group of SmFeN powder to obtain a first coated magnetic powder. The first coating typically contains zinc. The coating containing zinc means at least one of a coating containing metallic zinc and a coating containing a zinc alloy. The metallic zinc means unalloyed zinc.
[0090] As long as the first coating can be formed on the particle surfaces of the first particle group, the method of formation is not particularly limited. In the heat treatment step described below, the first coating on the particle surfaces of the first coated magnetic powder modifies the vicinity of the interface between the particle surfaces of the first particle group and the first coating, and the above-mentioned modified phase is formed (see FIG. 1). At the stage of obtaining the first coated magnetic powder, the vicinity of the interface between the particle surfaces of the first particle group and the first coating may or may not be modified. Typically, at the stage of obtaining the first coated magnetic powder, the vicinity of the interface between the particle surfaces of the first particle group and the first coating is not modified.
[0091] In the manufacturing method of the present disclosure, the particle powder of the first particle group and the powder containing zinc are not simply mixed, but a first coated magnetic powder is obtained in which a first coating containing zinc is formed on the particle surface of the first particle group, and the first coated magnetic powder is subjected to magnetic field compaction, pressure sintering, and heat treatment. Therefore, even if the content of the zinc component in the first coated magnetic powder is relatively low, a modified phase such as that shown in Figure 1 is obtained. This is because, compared to the case of simple mixing, in the manufacturing method of the present disclosure, the zinc component is advantageously brought into contact with the particle surface of the first particle group to form the first coating.
[0092] Specifically, when the content of the zinc component in the first coated magnetic powder is 3.0 mass% or more, 3.5 mass% or more, 4.0 mass% or more, or 5.0 mass% or more with respect to the total mass of the first coated magnetic powder and the second coated magnetic powder, most of the particle surfaces of the first particle group are covered with the modifier phase, and demagnetization can be suppressed, as shown in Figure 1. That is, the Fe-Zn alloy phase as the modifier phase is advantageously formed in a coating state on the particle surfaces of the first particle group.
[0093] On the other hand, if the content of the zinc component in the first coated magnetic powder is 10.0 mass% or less with respect to the total mass of the first coated magnetic powder and the second coated magnetic powder, the decrease in magnetization due to the use of the zinc component can be suppressed. From this viewpoint, the content of the zinc component in the first coated magnetic powder may be less than 10.0 mass%, 9.0 mass% or less, 8.0 mass% or less, 7.0 mass% or less, or 6.0 mass% or less with respect to the total mass of the first coated magnetic powder and the second coated magnetic powder.
[0094] Examples of the method for forming the first coating include a method using a rotary kiln furnace, a vapor deposition method, etc. Each of these methods will be briefly described below using the case where the first coating is a coating containing zinc as an example.
[0095] [Method using a rotary kiln] 4 is an explanatory diagram showing an example of a method for forming a zinc-containing coating (first coating) on the particle surface of SmFeN powder (first particle group) using a rotary kiln furnace. In the following description of the "method using a rotary kiln furnace", "SmFeN powder" means the particle powder of the first particle group unless otherwise specified.
[0096] The rotary kiln furnace 100 includes an agitating drum 110. The agitating drum 110 includes a material storage section 120, a rotating shaft 130, and an agitating plate 140. A rotating means (not shown) such as an electric motor is connected to the rotating shaft 130.
[0097] SmFeN powder 150 and zinc-containing powder 160 are charged into the material storage section 120. Thereafter, while the stirring drum 110 is rotating, the material storage section 120 is heated by a heater (not shown).
[0098] When the material storage unit 120 is heated to a temperature lower than the melting point of the zinc-containing powder 160, the zinc component of the zinc-containing powder 160 undergoes solid-phase diffusion on the surface of the particles of the SmFeN powder 150. As a result, a coating containing zinc is formed on the surface of the particles of the SmFeN powder 150. When the material storage unit 120 is heated to a temperature equal to or higher than the melting point of the zinc-containing powder 160, a molten solution of the zinc-containing powder 160 is obtained, and the molten solution comes into contact with the SmFeN powder 150. When the material storage unit 120 is cooled in this state, a coating containing zinc is formed on the surface of the particles of the SmFeN powder 150.
[0099] The operating conditions of the rotary kiln may be appropriately determined so as to obtain the desired coating.
[0100] The heating temperature of the material storage section may be, for example, (T-50)°C or higher, (T-40)°C or higher, (T-30)°C or higher, (T-20)°C or higher, (T-10)°C or higher, or T°C or higher, and may be (T+50)°C or lower, (T+40)°C or lower, (T+30)°C or lower, (T+20)°C or lower, or (T+10)°C or lower, where T is the melting point of the zinc-containing powder. When the zinc-containing powder is a powder containing metallic zinc, T is the melting point of zinc. When the zinc-containing powder is a powder containing a zinc alloy, T is the melting point of the zinc alloy.
[0101] The rotation speed (number of rotations) of the stirring drum may be, for example, 5 rpm or more, 6 rpm or more, 10 rpm or more, or 20 rpm or more, and may be 200 rpm or less, 100 rpm or less, or 50 rpm or less. The atmosphere during rotation is preferably an inert gas atmosphere to prevent oxidation of the powder and the formed coating. The inert gas atmosphere also includes a nitrogen gas atmosphere. The rotation time (coating treatment time) of the stirring drum can be appropriately determined so as to form a coating containing the desired zinc. The rotation time (coating treatment time) of the stirring drum may be, for example, 1 minute or more, 5 minutes or more, 10 minutes or more, 15 minutes or more, 30 minutes or more, 45 minutes or more, or 60 minutes or more, and may be 240 minutes or less, 210 minutes or less, 180 minutes or less, 150 minutes or less, 120 minutes or less, or 90 minutes or less.
[0102] After forming a coating containing zinc on the surface of the SmFeN powder particles, if the particles of the coated magnetic powder are bonded to each other, the bonded body may be pulverized. The pulverization method is not particularly limited, and examples thereof include a method of pulverizing using a ball mill, a jaw crusher, a jet mill, a cutter mill, and a combination thereof.
[0103] [Vapor deposition method] 5 is an explanatory diagram showing an example of a method for forming a coating (first coating) containing zinc on the particle surface of SmFeN powder (first particle group) by a vapor deposition method. In the following description of the "vapor deposition method", "SmFeN powder" means the particle powder of the first particle group unless otherwise specified.
[0104] The SmFeN powder 150 is stored in a first container 181, and the zinc-containing powder 160 is stored in a second container 182. The first container 181 is stored in a first heat treatment furnace 171, and the second container 182 is stored in a second heat treatment furnace 172. The first heat treatment furnace 171 and the second heat treatment furnace 172 are connected by a connecting path 173. The first heat treatment furnace 171 and the second heat treatment furnace 172 and the connecting path 173 are airtight, and a vacuum pump 180 is connected to the second heat treatment furnace 172.
[0105] After the insides of the first heat treatment furnace 171, the second heat treatment furnace 172 and the connecting passage 173 are depressurized by the vacuum pump 180, these insides are heated. Then, zinc-containing vapor is generated from the zinc-containing powder 160 stored in the second container 182. The zinc-containing vapor moves from the inside of the second container 182 to the inside of the first container 181, as shown by the solid line arrow in FIG.
[0106] The zinc-containing vapor that has moved to the inside of the first container 181 is cooled and forms (deposits) a coating on the particle surfaces of the SmFeN powder 150.
[0107] By making the first container 181 a rotating container, it can be made to function like a rotary kiln, and it is possible to further increase the coverage percentage of the coating formed on the particle surfaces of the SmFeN powder 150. The coverage percentage will be described later.
[0108] The conditions for forming a coating by the method shown in FIG. 5 may be appropriately determined so as to obtain a desired coating.
[0109] The temperature of the first heat treatment furnace (heating temperature of the SmFeN powder) may be, for example, 120°C or more, 140°C or more, 160°C or more, 180°C or more, 200°C or more, or 220°C or more, and may be 300°C or less, 280°C or less, or 260°C or less.
[0110] The temperature of the second heat treatment furnace (heating temperature of the powder containing zinc), where the melting point of the powder containing zinc is T, may be, for example, T°C or higher, (T+20)°C or higher, (T+40)°C or higher, (T+60)°C or higher, (T+80)°C or higher, (T+100)°C or higher, or (T+120)°C or higher, and may be (T+200)°C or lower, (T+180)°C or lower, (T+160)°C or lower, or (T+140)°C or lower. In addition, when the powder containing zinc is a powder containing metallic zinc, T is the melting point of zinc. In addition, when the powder containing zinc is a powder containing a zinc alloy, T is the melting point of the zinc alloy. Although the second container may store a bulk material containing zinc, it is preferable to store a powder containing zinc in the second container from the viewpoint of quickly melting the charge in the second container and generating steam containing zinc from the melt.
[0111] The first and second heat treatment furnaces are operated under reduced pressure to promote the generation of zinc-containing vapor and to prevent oxidation of the powder and the formed coating. The atmospheric pressure is, for example, 1×10 -5 MPa or less is preferable, and 1×10 -6 MPa or less is more preferable, and 1×10 -7 On the other hand, even if the pressure is not excessively reduced, there is no practical problem, and as long as the above-mentioned atmospheric pressure is satisfied, the atmospheric pressure is preferably 1×10 -8 MPa or more.
[0112] When the first container is a rotating container, its rotation speed (number of rotations) may be, for example, 5 rpm or more, 10 rpm or more, or 20 rpm or more, and may be 200 rpm or less, 100 rpm or less, or 50 rpm or less.
[0113] In the deposition method, after forming a coating containing zinc on the surface of the SmFeN powder particles, if the particles of the coated magnetic powder are bonded to each other, the bonded body may be pulverized. The pulverization method is not particularly limited, and examples thereof include a method of pulverizing using a ball mill, a jaw crusher, a jet mill, a cutter mill, and a combination thereof.
[0114] [Zinc component coverage] Even when the first coated magnetic powder is obtained by forming the first coating on the particle surface of the SmFeN powder particles (first particle group) by any method, it is preferable that the coating rate of the zinc component in the first coated magnetic powder is high. This is because if the coating rate of the zinc component is high, the coating rate of the modified phase formed on the particle surface of the first particle group in the rare earth magnet will be high after the heat treatment process described below, and the coercive force will be advantageously improved. Next, a method for determining the coating rate of the zinc component will be described.
[0115] In the first coated magnetic powder, the coverage of the zinc component is the ratio (percentage) of the zinc component covering the entire particle surface of the first particle group. The coverage (%) of the zinc component is determined as follows. In the following explanation of the "coverage of the zinc component", unless otherwise specified, "SmFeN powder" means the particle powder of the first particle group.
[0116] Using X-ray photoelectron spectroscopy (XPS), composition information is obtained for the SmFeN powder (first particle group) and the constituent elements of the first coating for the first coated magnetic powder. Then, the coating rate (%) of the zinc component is calculated using the following formula.
[0117] Coverage rate of zinc component (%)=[(total of composition information for each of the constituent elements of the first coating) / {(total of composition information for each of the constituent elements of the SmFeN powder (first particle group))+(total of composition information for each of the constituent elements of the first coating)}]×100
[0118] For example, when the SmFeN powder is composed of Sm, Fe, and N, the sum of the composition information for each of the constituent elements of the SmFeN powder means the sum of the composition information for each of Sm, Fe, and N. Even when the SmFeN powder contains elements other than Sm, Fe, and N, the content ratio of elements other than Sm, Fe, and N is small. Therefore, even when the SmFeN powder contains elements other than Sm, Fe, and N, the sum of the composition information for each of the constituent elements of the SmFeN powder may be approximated by the sum of the composition information for each of Sm, Fe, and N. In addition, when the first coating is, for example, metallic zinc, the sum of the composition information for each of the constituent elements of the first coating means the composition information for Zn. When the first coating is, for example, a zinc alloy, the sum of the composition information for each of the constituent elements of the first coating means the sum of the composition information for Zn and each of the alloying elements. When the zinc alloy is, for example, a Zn-Al alloy, the sum of the composition information for each of the constituent elements of the first coating means the sum of the composition information for Zn and each of the alloying elements.
[0119] For example, the composition information about Zn means the mass of Zn present, which is obtained by measuring the XPS spectrum of the first coated magnetic powder and calculating the peak intensity of the obtained XPS spectrum. In the case where the SmFeN powder is composed of, for example, Sm, Fe, and N, and the first coating is, for example, zinc, the coverage rate (%) of the zinc component is calculated as follows. Coverage rate of zinc component (%) = (abundant mass of Zn) / (total of abundant mass of Sm, Fe, N, and Zn) × 100
[0120] The coverage of the zinc component thus determined is preferably 80% or more, 83% or more, 90% or more, or 94% or more, and ideally 100%.
[0121] The particles of the SmFeN powder are very hard. In comparison, the particles of the powder containing zinc are generally soft. For this reason, when the SmFeN powder and the powder containing zinc are merely mixed, the deformed particles of the powder containing zinc may adhere to the particle surface of the SmFeN powder, forming a first coating. However, it is difficult to stably achieve a coating rate of the zinc component of 80% or more by merely mixing. Therefore, when preparing the first coated magnetic powder, it is preferable to adopt the method using a rotary kiln furnace or the deposition method as described above.
[0122] As described above, the first coating is typically a coating containing zinc, and the coating containing zinc means at least one of a coating containing metallic zinc and a coating containing a zinc alloy. 2 Expressed as M 2 Alternatively, an element that is alloyed with Zn (zinc) to lower the melting temperature of the zinc alloy below the melting point of Zn and an unavoidable impurity element may be selected. This improves the sinterability in the pressure sintering process described below, and improves the modifiability in the heat treatment process described below. 2 As for the metals, Zn and M 2 Elements that form eutectic alloys with M 2 Typically, Sn, Mg, and Al, as well as combinations thereof, are included. Sn is tin, Mg is magnesium, and Al is aluminum. Elements that do not lower the melting point or impair the properties of the resulting product are also included. 2 The inevitable impurity element refers to an impurity element, such as an impurity contained in a raw material of a zinc-containing powder, whose inclusion cannot be avoided, or whose avoidance would result in a significant increase in production costs.
[0123] Zn-M 2 In the zinc alloy represented by the formula 2 The ratio (molar ratio) of M to the entire zinc alloy may be appropriately determined so that the sintering temperature and / or the heat treatment temperature of the sintered body are appropriate.2 The ratio (molar ratio) of may be, for example, 0.05 or more, 0.10 or more, or 0.20 or more, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less.
[0124] The zinc-containing powder used in the above-mentioned "Method using a rotary kiln furnace" and "Vapor deposition method" may contain, in addition to metallic zinc and / or zinc alloy, any substance having a binder function and / or a modifying function and other functions, as long as the effect of the present invention is not impaired. Examples of other functions include a function of improving corrosion resistance.
[0125] The particle size of the zinc-containing powder is not particularly limited, but it is preferable that the particle size is smaller than that of the SmFeN powder. This makes it easier for the zinc-containing powder particles to spread between the particles of the SmFeN powder, especially when a rotary kiln is used. The particle size of the zinc-containing powder is, for example, D 50 (median diameter) may be 0.1 μm or more, 0.5 μm or more, or 1.0 μm or more, and may be 12.0 μm or less, 11.0 μm or less, 10.0 μm or less, 9.0 μm or less, 8.0 μm or less, 7.0 μm or less, 6.0 μm or less, 5.0 μm or less, 4.0 μm or less, or 2.0 μm or less. 50 The median diameter is measured, for example, by a dry laser diffraction / scattering method.
[0126] In particular, when using a rotary kiln, it is preferable that the oxygen content of the zinc-containing powder is low, since it can absorb a large amount of oxygen in the SmFeN powder. From this viewpoint, the oxygen content of the zinc-containing powder is preferably 5.0 mass% or less, more preferably 3.0 mass% or less, and even more preferably 1.0 mass% or less, based on the entire zinc-containing powder. On the other hand, extremely reducing the oxygen content of the modifier powder leads to an increase in manufacturing costs. For this reason, the oxygen content of the zinc-containing powder may be 0.1 mass% or more, 0.2 mass% or more, or 0.3 mass% or more, based on the entire zinc-containing powder.
[0127] <Second coated magnetic powder preparation process> A second coating is formed on the particle surface of the second particle group of SmFeN powder to obtain a second coated magnetic powder. There is no particular restriction on the second coating, so long as it can prevent the particle surface of the second particle group from being modified by the adjacent first coating and does not adversely affect the magnetic properties of the rare earth magnet obtained by the manufacturing method of the present disclosure. Such a second coating contains, for example, phosphoric acid, but is not limited thereto.
[0128] When the second coating is a coating containing phosphoric acid, the content of phosphoric acid in the second coating may be 40 mass% or more, 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, or 90 mass% or more, or may be 100 mass% based on the entire second coating. When the second coating is a coating containing phosphoric acid, the thickness thereof may be 5 to 100 nm.
[0129] As long as the second coating can be formed on the particle surfaces of the second particle group, the method for forming the second coating is not particularly limited.
[0130] When a coating containing phosphoric acid is formed as the second coating on the particle surfaces of the second particle group, the following method can be mentioned as a method for forming the second coating.
[0131] The particles of the second particle group are subjected to a phosphoric acid treatment to form a passivation film having a PO bond on the particle surface of the second particle group. In the phosphoric acid treatment process, a phosphoric acid treatment agent is reacted with the particles of the second particle group. Examples of the phosphoric acid treatment agent include inorganic phosphoric acids and organic phosphoric acids such as phosphate salts such as orthophosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, zinc phosphate, and calcium phosphate, hypophosphorous acid, hypophosphite salts, pyrophosphoric acid, and polyphosphoric acid. These phosphoric acid sources are basically dissolved in water or an organic solvent such as an IPN, and the particles of the second particle group are placed in a phosphoric acid bath to which a reaction accelerator such as nitrate ions and a crystal refiner such as V ions, Cr ions, and Mo ions are added as necessary, to form a passivation film having a PO bond on the particle surface of the second particle group.
[0132] <Mixing process> The first coated magnetic powder and the second coated magnetic powder are mixed to obtain a mixed powder. The mixing method is not particularly limited, and examples thereof include a method of mixing using an agitator mixer and a V-type mixer, and these may be combined.
[0133] <Magnetic field forming process> The mixed powder is compressed in a magnetic field to obtain a magnetically compacted body, which gives orientation to the magnetically compacted body and anisotropy to the resulting product (rare earth magnet), improving remanence.
[0134] The magnetic field molding method may be a well-known method such as a method of compression molding the mixed powder using a mold around which a magnetic field generator is installed. The molding pressure may be, for example, 10 MPa or more, 20 MPa or more, 30 MPa or more, 50 MPa or more, 100 MPa or more, or 150 MPa or more, and may be 1500 MPa or less, 1000 MPa or less, or 500 MPa or less. The time for applying the above-mentioned molding pressure may be, for example, 0.5 minutes or more, 1 minute or more, or 3 minutes or more, and may be 10 minutes or less, 7 minutes or less, or 5 minutes or less. The strength of the applied magnetic field may be, for example, 500 kA / m or more, 1000 kA / m or more, 1500 kA / m or more, or 1600 kA / m or more, and may be 20000 kA / m or less, 15000 kA / m or less, 10000 kA / m or less, 5000 kA / m or less, 3000 kA / m or less, or 2000 kA / m or less. Examples of the method of applying the magnetic field include a method of applying a static magnetic field using an electromagnet and a method of applying a pulse magnetic field using an alternating current. In addition, in order to suppress oxidation of the mixed powder, it is preferable that the magnetic field molding is performed in an inert gas atmosphere. The inert gas atmosphere includes a nitrogen gas atmosphere.
[0135] <Pressure sintering process> The magnetic field compact is pressure-sintered to obtain a sintered body. The pressure-sintering method is not particularly limited, and any known method can be applied. As the pressure-sintering method, for example, a method is mentioned in which a die having a cavity and a punch capable of sliding inside the cavity are prepared, the magnetic field compact is inserted inside the cavity, and the magnetic field compact is sintered while applying pressure to the magnetic field compact with the punch. In this method, typically, the die is heated using a high-frequency induction coil. Alternatively, a spark plasma sintering (SPS) method may be used.
[0136] The pressure sintering conditions may be appropriately selected so that the magnetic compact can be sintered (hereinafter sometimes referred to as "pressure sintered") while applying pressure to the magnetic compact.
[0137] If the sintering temperature is 300°C or higher, the sintering of the mixed powder of the first coated magnetic powder and the second coated magnetic powder proceeds advantageously in the magnetic field compact. From this viewpoint, the sintering temperature may be, for example, 310°C or higher, 320°C or higher, 340°C or higher, or 350°C or higher. On the other hand, if the sintering temperature is 430°C or lower, the Fe on the particle surface of the first particle group of the first coated magnetic powder and the zinc component in the first coating of the first coated magnetic powder do not diffuse excessively between each other. As a result, there is no problem with the heat treatment process described later, or there is no adverse effect on the magnetic properties of the obtained sintered body. From this viewpoint, the sintering temperature may be 420°C or lower, 410°C or lower, 400°C or lower, 390°C or lower, 380°C or lower, 370°C or lower, or 360°C or lower. From the viewpoint of sintering the mixed powder in a relatively short time during pressure sintering and minimizing interdiffusion between the Fe on the particle surfaces of the first particle group of the first coated magnetic powder and the zinc component in the first coating of the first coated magnetic powder, the sintering temperature may be 350°C or more, 360°C or more, or 370°C or more, and may be 400°C or less, 390°C or less, or 380°C or less.
[0138] The sintering pressure may be appropriately selected so that the density of the sintered body can be increased. The sintering pressure may typically be 100 MPa or more, 200 MPa or more, 400 MPa or more, 500 MPa or more, 600 MPa or more, 800 MPa or more, or 1000 MPa or more, and may be 2000 MPa or less, 1800 MPa or less, 1600 MPa or less, 1500 MPa or less, 1300 MPa or less, or 1200 MPa or less. In the above-mentioned range, the higher the pressure, the more advantageous it is for improving the density of the sintered body, but the frequency of contact between particles in the magnetic compact increases during sintering, and cracks and / or deformations are likely to occur in the sintered body itself and / or the particles in the sintered body, and as a result, distortions are likely to remain in the sintered body itself and / or the particles in the sintered body. The increase in density of the sintered body contributes to the improvement of remanent magnetization, but if distortions remain in the sintered body itself and / or the particles in the sintered body, the saturation magnetization decreases, and thus the remanent magnetization decreases. For these reasons, the sintering pressure is preferably 200 MPa or more, 400 MPa or more, 500 MPa or more, 600 MPa or more, 800 MPa or more, or 1000 MPa or more, and 1500 MPa or less, 1300 MPa or less, or 1200 MPa or less.
[0139] The sintering time may be appropriately determined in consideration of the relationship with the sintering temperature, etc., so that the mixed powder in the magnetic compact can be sintered while avoiding excessive mutual diffusion between the Fe on the particle surface of the first particle group of the first coated magnetic powder and the zinc component in the first coating of the first coated magnetic powder. The sintering time does not include the temperature rise time until the heat treatment temperature is reached. The sintering time may be, for example, 1 minute or more, 2 minutes or more, or 3 minutes or more, and 30 minutes or less, 20 minutes or less, 10 minutes or less, or 5 minutes or less. When the sintering time is within the above-mentioned range, the sintering temperature is set to the melting point of zinc or less, that is, 300°C or more, 310°C or more, 320°C or more, 340°C or more, or 350°C or more, and 400°C or less, 390°C or less, 380°C or less, 370°C or less, or 360°C or less, thereby preventing the zinc component from excessively diffusing on the surface of the SmFeN particles, and as a result, the decrease in remanence can be suppressed.
[0140] After the sintering time has elapsed, the sintered body is cooled to terminate the sintering. A faster cooling rate can suppress oxidation of the sintered body and can also suppress coarsening of the magnetic phase in the sintered body. The cooling rate may be, for example, 0.5°C / sec or more, 1°C / sec or more, or 10°C / sec or more, and may be 200°C / sec or less, 150°C / sec or less, 100°C / sec or less, or 50°C / sec or less.
[0141] The sintering atmosphere is preferably an inert gas atmosphere to suppress oxidation of the magnetic compact and the sintered body. Examples of the inert gas atmosphere include an argon gas atmosphere and a nitrogen gas atmosphere. Alternatively, sintering may be performed in a vacuum.
[0142] <Heat treatment process> The sintered body is subjected to a heat treatment, whereby, during the heat treatment, in the first coated magnetic powder in the sintered body, the first coating advances the modification of the particle surfaces of the first particle group, and, in the second coated magnetic powder in the sintered body, the second coating inhibits the particle surfaces of the second particle group from being modified by the adjacent first coating.
[0143] As the modification progresses, a coating-like modified phase (Fe-Zn alloy phase) is formed on the particle surfaces of the first particle group, and the particles of the first particle group are bonded together more strongly (hereinafter, this may be referred to as "solidifying" or "solidification"), and at the same time, the modification is promoted. At this time, due to the solidification of the particles of the first particle group, the particles of the second particle group present between the first particle group are also bonded strongly to the particles of the first particle group.
[0144] When the first particle group and the second particle group contain fine powder particles, an Fe-Zn alloy phase is formed in almost the entire fine powder particle, and much of the Fe-Zn alloy phase is integrated with a coating-like modified phase (Fe-Zn alloy phase) formed on the particle surfaces of the first particle group.
[0145] As described above, in the manufacturing method of the present disclosure, even if the modification of the first coated magnetic powder progresses, in the second coated magnetic powder, the particle surface of the second particle group is suppressed from being modified by the adjacent first coating by the second coating. This promotes the improvement of the coercive force of the first particle group and suppresses the improvement of the coercive force of the second particle group. Since the first particle group has a large particle size, it has a low coercive force without modification, whereas the second particle group has a small particle size and has a high coercive force even without modification. As the improvement of the coercive force of the first particle group progresses and the improvement of the coercive force of the second particle group is suppressed, the difference in coercive force between the first particle group and the second particle group becomes smaller, and the squareness, especially the squareness at high temperatures, is improved (see FIG. 3). As a result, the sintered body after heat treatment (rare earth magnet obtained by the manufacturing method of the present disclosure) is less likely to demagnetize in an environment where an external magnetic field is applied, especially at high temperatures.
[0146] Regarding the heat treatment, it is ideal to heat treat until all of the particle surfaces of the first particle group are covered with the modified phase, that is, until 100% of the particle surfaces of the first particle group are covered with the modified phase (modified phase coverage rate 100%). However, heat treatment may be performed aiming to cover 75% or more, 76% or more, 80% or more, or 90% or more of the particle surfaces of the first particle group with the modified phase. This provides practically advantageous high-temperature demagnetization characteristics. The method for measuring the modified phase coverage rate is as follows. In this specification, unless otherwise specified, the description regarding the modified phase coverage rate is based on the following measurement method (investigation method).
[0147] The cross section of the sintered body after the heat treatment is polished, and the polished surface is subjected to component analysis (surface analysis) for Fe and Zn, respectively, to obtain an Fe mapping image and a Zn mapping image. The Fe mapping image and the Zn mapping image are superimposed to obtain an integrated mapping image. In the integrated mapping image, the region of the SmFeN powder (first particle group) is identified, and the perimeter length L of the SmFeN powder (first particle group) is measured. In the integrated mapping image, the length L of the portion of the perimeter of the SmFeN powder (first particle group) sandwiched between the Fe detection region and the Zn detection region is measured. c and the length L of the part sandwiched between the Fe detection area and the non-detection area. gThe non-detection region means a region where neither Fe nor Zn is detected. The modified phase coverage rate (%) is then calculated using the following formula (1). Modified phase coverage (%) = L c / (L c +L g )×100...Equation (1)
[0148] In the above formula (1), (L c +L g ) means the total perimeter of the particle surface of the first particle group in the cross section, and L c means the coating length (modified phase length) of the particle surfaces of the first particle group.
[0149] As shown in Fig. 1, the sintered body after heat treatment (rare earth magnet 90 obtained by the manufacturing method of the present disclosure) has a structure in which the modifier phase 20 is formed on the particle surfaces of the first particle group 11, but the modifier phase 20 is substantially not formed on the particle surfaces of the second particle group 12. For convenience, Fig. 1 shows an example in which the modifier phase coverage is 100%, but this is not limiting and the above-mentioned modifier phase coverage may be used.
[0150] 1, in the sintered body after the heat treatment (rare earth magnet 90 obtained by the manufacturing method of the present disclosure), substantially no coating is observed on the particle surfaces of the second particle group 12, but this is not limited to this. That is, it is believed that the second coating 42 present in the sintered body before the heat treatment typically decomposes into the elements that make up the second coating 42, and the elements are dispersed on the modified phase 20 or the particle surfaces of the second particle group 12, but this is not limited to this. For this reason, in the sintered body after the heat treatment (rare earth magnet 90 obtained by the manufacturing method of the present disclosure), the second coating may remain on some or all of the particle surfaces of the second particle group.
[0151] The heat treatment temperature can be, for example, 350°C or higher to obtain the above-mentioned modified phase. From this viewpoint, the heat treatment temperature may be 360°C or higher, 370°C or higher, or 380°C or higher. On the other hand, if the heat treatment temperature is 410°C or lower, Fe and Zn do not diffuse excessively between each other. However, although solidification, modification, and harmlessness of fine powder particles can be achieved at a heat treatment temperature of 410°C, knicks occur, so the heat treatment temperature is preferably 400°C or lower or 390°C or lower. Note that knicks refer to a sudden decrease in magnetization in response to a slight decrease in magnetic field in a region other than the region showing the coercive force of the magnetization-magnetic field curve (MH curve).
[0152] The heat treatment time is not particularly limited, but may be determined by the following formulas (2) and (3) assuming that the heat treatment temperature is x° C. and the heat treatment time is y hours. y≧-0.32x+136...Equation (2) 350≦x≦410...Equation (3)
[0153] The above equations (2) and (3) have been confirmed by experiments and demonstrate that the higher the heat treatment temperature, the shorter the heat treatment time with respect to solidification and the formation of the above-mentioned modified phase.
[0154] From the viewpoint of increasing the modified phase coverage as much as possible, in the above formula (2), y≧−0.32x+137 is more preferable, y≧−0.32x+140 is even more preferable, and y≧−0.32x+145 is even more preferable.
[0155] The above-mentioned modified phase is formed by alloying the α-Fe phase present on the particle surface of the first particle group and the zinc component in the first coating in the first coated magnetic powder. To form the modified phase, the heat treatment time may typically be 3 hours or more, 4 hours or more, 5 hours or more, 8 hours or more, 10 hours or more, 12 hours or more, 15 hours or more, 17 hours or more, or 20 hours or more. On the other hand, the amount of α-Fe phase present on the particle surface of the first particle group is limited, and the depth to which the zinc component in the first coating diffuses into the particles of the first particle group is also limited. Therefore, even if the heat treatment is performed for an excessively long time, the formation of the modified phase is saturated. From this viewpoint, the heat treatment time y (hours) is preferably 40 hours or less, 35 hours or less, 30 hours or less, 25 hours or less, or 24 hours or less.
[0156] In order to suppress oxidation of the sintered body, it is preferable to heat treat the sintered body in a vacuum or in an inert gas atmosphere. The inert gas atmosphere includes a nitrogen gas atmosphere. The heat treatment of the sintered body may be performed in the mold used for pressure sintering, but in that case, no pressure is applied to the sintered body during the heat treatment. If the above-mentioned heat treatment conditions are satisfied, the normal magnetic phase decomposes to generate an α-Fe phase, and as a result of this generation, it is possible to suppress excessive interdiffusion of Fe and Zn. When the heat treatment is performed in a vacuum, the absolute pressure of the atmosphere is 1×10 -7 Pa or more, 1×10 -6 Pa or more, or 1×10 -5 Pa or more, and -2 Pa or less, 1×10 -3 Pa or less, or 1×10 -4 Pa or less.
[0157] 《Transform》 In addition to what has been described above, the manufacturing method of the present disclosure can be modified in various ways within the scope of the claims.
[0158] For example, when the first particle group and / or the second particle group include fine particles, the D of the first particle group and the second particle group is 50As long as the above-mentioned range is satisfied, a part or all of the fine particles may be removed in advance. There is no particular limitation on the fine particle removal operation (fine particle removal method). Examples of the fine particle removal operation (fine particle removal method) include a method using a centrifugal field classifier, a method using a sieve, a method using a magnetic field, and a method using static electricity. A combination of these methods may also be used. By removing the fine particles, the density of the molded body (rare earth magnet) can be further increased, and the magnetization and mechanical strength can be further increased. EXAMPLES
[0159] The manufacturing method of the present disclosure will be described in more detail below with reference to examples and comparative examples. Note that the manufacturing method of the present disclosure is not limited to the conditions used in the following examples.
[0160] <Sample preparation> Samples of Examples 1 to 8 and Comparative Examples 1 to 9 were prepared in the following manner.
[0161] Examples 1 to 8 and Comparative Examples 1 to 6 5.0 kg of FeSO4·7H2O was mixed and dissolved in 2.0 kg of pure water. 0.49 kg of Sm2O3, 0.74 kg of 70% sulfuric acid, and 0.035 kg of La2O3 were then added and thoroughly stirred to completely dissolve. Next, pure water was added to the resulting solution, and the final Fe concentration was adjusted to 0.726 mol / L and the Sm concentration to 0.112 mol / L to create the SmFeLa sulfuric acid solution.
[0162] [Precipitation process] The entire amount of the prepared SmFeLa sulfate solution was dropped into 20 kg of pure water kept at a temperature of 40°C for 70 minutes from the start of the reaction while stirring, and at the same time, 15% ammonia solution was dropped to adjust the pH to 7-8. This resulted in a slurry containing SmFeLa hydroxide. The obtained slurry was washed with pure water by decantation, and the hydroxide was separated into solid and liquid. The separated hydroxide was dried in an oven at 100°C for 10 hours.
[0163] [Oxidation process] The hydroxide obtained in the precipitation process was calcined in air at 1000°C for 1 hour. After cooling, red SmFeLa oxide was obtained as raw powder.
[0164] [Pretreatment process] 100 g of SmFeLa oxide was placed in a steel container so that the bulk thickness was 10 mm. The container was placed in a furnace and the pressure was reduced to 100 Pa. Then, the container was heated to the pretreatment temperature of 850°C while introducing hydrogen gas, and was maintained for 15 hours. The oxygen concentration was measured by non-dispersive infrared absorption (ND-IR) (EMGA-820 manufactured by Horiba, Ltd.) and found to be 5 mass%. This revealed that the oxygen bonded to Sm was not reduced, and 95% of the oxygen bonded to Fe was reduced, resulting in a black partial oxide.
[0165] [Reduction process] 60 g of the partial oxide obtained in the pretreatment process and 19.2 g of metallic calcium with an average particle size of about 6 mm were mixed and placed in a furnace. After evacuating the furnace, argon gas (Ar gas) was introduced. The temperature was raised to 1090°C and held for 45 minutes, and then cooled to obtain SmFe powder particles.
[0166] [Nitriding process] Subsequently, the temperature inside the furnace was cooled to 100°C, and then the furnace was evacuated to a vacuum, and while introducing nitrogen gas, the temperature was raised to a first temperature of 430°C and held for 3 hours. Then, the temperature was raised to a second temperature of 500°C and held for 1 hour, and then cooled to obtain a lump-shaped product containing magnetic powder particles.
[0167] [Post-processing process] The aggregated product obtained in the nitriding step was poured into 3 kg of pure water and stirred for 30 minutes. After standing, the supernatant was drained by decantation. The process of pouring into pure water, stirring and decantation was repeated 10 times. Next, 2.5 g of 99.9% acetic acid was poured into the product and stirred for 15 minutes. After standing, the supernatant was drained by decantation. The process of pouring into pure water, stirring and decantation was repeated twice.
[0168] [Acid treatment process] A 6% aqueous hydrochloric acid solution was added to 100 parts by mass of the powder obtained in the post-treatment step so that the hydrogen chloride content was 4.3 parts by mass, and the mixture was stirred for 1 minute. After being allowed to stand, the supernatant was drained by decantation. The process of pouring into pure water, stirring, and decantation was repeated twice. After solid-liquid separation, the mixture was vacuum dried at 80°C for 3 hours to obtain Sm. 9.2 Fe 77.1 N 13.59 La 0.11 A SmFeN powder having the following composition was obtained.
[0169] The SmFeN powder was packed into a sample container together with paraffin wax, and the paraffin wax was melted in a dryer, after which the easy axis of magnetization was aligned in an orientation magnetic field of 16 kA / m. This magnetically oriented sample was pulse-magnetized in a magnetizing magnetic field of 32 kA / m, and the magnetic properties were measured at room temperature using a VSM (vibrating sample magnetometer) with a maximum magnetic field of 16 kA / m, revealing a residual magnetization of 1.44 T and a coercive force of 750 kA / m.
[0170] The SmFeN powder obtained as described above was classified to obtain a powder of the first particle group and a powder of the second particle group. 50 ) was as shown in Table 1-1. The ratio of the total volume of the first particle group to the total volume of the second particle group (total volume of the first particle group:total volume of the second particle group) was as shown in Table 1-1. Table 1-1 also shows the particle remanent magnetization σ r and particle coercivity H c are also listed.
[0171] A first coating was formed on the particle surface of the first particle group by the method shown in FIG. 4 to obtain a first coated magnetic powder. Metallic zinc powder was prepared as a powder containing zinc so that the first coating was a coating containing zinc. 50 The particle size was 0.5 μm. The purity of the metallic zinc powder was 99.5% by mass.
[0172] The zinc content ratio relative to the total mass of the first coated magnetic powder and the second coated magnetic powder, i.e., the amount of metal zinc powder charged into the rotary kiln together with the particles of the first particle group, relative to the total mass of the first coated magnetic powder and the second coated magnetic powder, was as shown in Table 1-1. The treatment conditions in the rotary kiln were as follows: the atmosphere was a nitrogen gas atmosphere, the treatment temperature was 380°C, the treatment time was 1 minute, and the rotation speed of the stirring drum was 6 rpm. The zinc component coverage rate of the coated magnetic powder particles thus obtained is also shown in Table 1-1.
[0173] A coating containing phosphoric acid was formed as a second coating on the particle surfaces of the second particle group to prepare a second coated magnetic powder. The coating containing phosphoric acid was formed by carrying out a dispersion step and a surface treatment step as a preparation step before the phosphoric acid treatment step. The details of the dispersion step, the surface treatment step, and the phosphoric acid treatment step are as follows.
[0174] [Dispersion process] The powder of the second particle group and the media were placed in a container so that the powder of the second particle group was 5 volume % and the media (iron-core nylon media, diameter 10 mm, Vickers constant of nylon coating 7, specific gravity 7.48 g / cm3) was 60 volume % relative to the volume of the container used for the vibration mill. The mixture was dispersed in a nitrogen atmosphere for 60 minutes using the vibration mill to obtain an intermediate powder.
[0175] [Surface treatment process] The obtained intermediate powder was put into pure water and stirred for 1 minute. An acid solution was added to this slurry to perform etching. A hydrochloric acid solution was used as the acid solution. 50g or more of 5% hydrochloric acid was added to 100g of the intermediate powder while stirring. After confirming that the pH was 3 or more, decantation was performed until the electrical conductivity of the slurry was 100μS / cm or less.
[0176] [Phosphating process] A phosphoric acid solution was added to the obtained slurry. The phosphoric acid solution was added in an amount of 1 mass% as PO4 relative to the solid content of the particles of the second particle group. After stirring for 5 minutes and performing solid-liquid separation, the mixture was vacuum-dried at 120°C for 3 hours to obtain a second coated magnetic powder having a coating containing phosphoric acid.
[0177] The first coated magnetic powder and the second coated magnetic powder were mixed to obtain a mixed powder. The mixed powder was compression molded in a magnetic field to obtain a magnetically molded body. The pressure for compression molding was 50 MPa. The time for applying this pressure was 1 minute. The magnetic field applied was 1600 kA / m. The compression molding was performed in a nitrogen atmosphere.
[0178] The magnetic field compact was pressure sintered. Pressure sintering was performed in an argon gas atmosphere (97,000 Pa) using a high-frequency induction coil. The sintering temperature was 380°C, the sintering pressure was 500 MPa, and the sintering pressure was applied for 5 minutes.
[0179] The sintered body was placed in a vacuum (10 -2 The heat treatment was performed at a pressure of 380° C. for 24 hours.
[0180] Comparative Example 7 The zinc component coverage rate of the particle surface of the first particle group was 72%, the second coating film was not formed on the particle surface of the second particle group, and the σ r A sample of Comparative Example 7 was prepared similarly to Example 3, except that the molecular weight was 141 emu / g.
[0181] Comparative Example 8 A sample of Comparative Example 8 was prepared in the same manner as in Example 1, except that the magnetic powder contained only the first particle group and did not contain the second particle group.
[0182] Comparative Example 9 A sample of Comparative Example 9 was prepared in the same manner as in Example 3, except that the magnetic powder contained only the first particle group and did not contain the second particle group.
[0183] "evaluation" The modified phase coverage and magnetic properties of each sample were measured. The magnetic properties were measured at room temperature and at 120°C using a vibrating sample magnetometer (VSM). Demagnetization was measured at 120°C by measuring the residual magnetization B r When the magnetization is reduced by 10% from k The density of the sintered body after the heat treatment was measured by the Archimedes method.
[0184] The evaluation results are shown in Tables 1-1 and 1-2. In Table 1-2, the residual magnetization and coercive force are the results of measurements taken at room temperature.
[0185] [Table 1-1]
[0186] [Table 1-2]
[0187] From Tables 1-1 and 1-2, it can be seen that the residual magnetization of all the samples in the examples was 0.9 T or more, and the H k From this, it can be seen that the rare earth magnet obtained by the manufacturing method of the present disclosure has excellent magnetization and is resistant to demagnetization in an environment where an external magnetic field is applied, particularly at high temperatures.
[0188] In contrast, in the samples of Comparative Examples 1 and 2, d2 / d1 is large, and as shown in FIG. 6, the particle diameter of the second particle group 12 is large, so the density is low and the magnetization is low. In the samples of Comparative Examples 3 to 5, the total volume ratio of the first particle group 11 to the second particle group 12 is not appropriate, and as shown in FIG. 7, the volume of the second particle group 12 is excessive, so the density is low and the magnetization is low. In the sample of Comparative Example 6, the zinc content in the first coated magnetic powder is low, so the modification of the particle surfaces of the first particle group is insufficient, and H k In the sample of Comparative Example 7, since the second coating was not formed on the particle surfaces of the second particle group, as shown in FIG. 8, a thick modified phase 20 was formed on the particle surfaces of the second particle group, and the modification was excessive, so that H kThe samples of Comparative Examples 8 and 9 contain only the first particle group 11 and do not contain the second particle group 12, as shown in FIG.
[0189] The above results confirm the effectiveness of the manufacturing method for rare earth magnets according to the present disclosure. [Explanation of symbols]
[0190] 10 SmFeN powder 11 First particle group 12 Second particle group 20 Modification Phase 30 Sintered body 31 First coated magnetic powder 32 Second coated magnetic powder 41 First coating 42 Second coating 90 Rare Earth Magnets 100 Rotary Kiln Furnace 110 Mixing drum 120 Material Storage Section 130 Rotational Axis 140 Stirring plate 150 SmFeN powder 160 Powder containing zinc 171 No. 1 Heat Treatment Furnace 172 No. 2 heat treatment furnace 173 Connecting road 180 Vacuum Pump 181 1st container 182 Second container
Claims
1. Contains Sm, Fe, and N, and at least a portion of Th 2 Zinc 17 Type and Th 2 Ni 17 A method for producing a rare earth magnet having a magnetic phase having any one of the crystal structures of the above types, comprising the steps of: Providing a magnetic powder comprising a first group of particles and a second group of particles; forming a first coating on the surfaces of the particles of the first particle group of the magnetic powder to obtain a first coated magnetic powder; forming a second coating on the surfaces of the particles of the second particle group of the magnetic powder to obtain a second coated magnetic powder; mixing the first coated magnetic powder and the second coated magnetic powder to obtain a mixed powder; The mixed powder is compression-molded in a magnetic field to obtain a magnetically molded body. Pressure sintering the magnetic field compact to obtain a sintered body; and heat treating the sintered body; Including, Particle size distribution D of the first particle group 50 But, d 1 The particle size distribution D of the second particle group is expressed in μm. 50 But, d 2 Expressed in μm, The above d 1 and the above d 2 However, 0.350≦d 2 / d 1 The relationship of ≦0.500 is satisfied, a ratio of a total volume of the first particle group to a total volume of the second particle group (total volume of the first particle group:total volume of the second particle group) is in the range of 9:1 to 4:1, the first coating contains zinc, and the content of the zinc component in the first coated magnetic powder is 3.0 mass% or more and 10.0 mass% or less with respect to the total mass of the first coated magnetic powder and the second coated magnetic powder; and During the heat treatment, the first coating film causes the particle surfaces of the first particle group to be modified, and the second coating film suppresses the particle surfaces of the second particle group from being modified by the adjacent first coating film. A method for manufacturing rare earth magnets.
2. The method for producing a rare earth magnet according to claim 1 , wherein the second coating contains phosphoric acid.
3. 3. The method for producing a rare earth magnet according to claim 1, wherein the heat treatment is carried out until an Fe-Zn alloy phase is formed on 75% or more of the surfaces of the particles of the first particle group in the sintered body.
4. The method for producing a rare earth magnet according to any one of claims 1 to 3, wherein the heat treatment is carried out at a temperature of 350°C or higher and 410°C or lower.
5. The method for producing a rare earth magnet according to any one of claims 1 to 4, wherein the heat treatment is carried out for 3 hours or more and 40 hours or less.
6. The method for producing a rare earth magnet according to any one of claims 1 to 5, wherein the magnetic compact is pressure sintered at a pressure of 200 MPa to 1500 MPa and a temperature of 300°C to 400°C for 1 minute to 30 minutes.
Citation Information
Patent Citations
Anisotropic magnetic powder and production method therefor
JP2017117937A
Magnet and manufacturing method thereof
JP2018170451A
Method of producing rare earth magnet
JP2019012796A
Method of manufacturing rare earth magnet
JP2020053440A
Manufacturing method for anisotropic magnetic powder and anisotropic magnetic powder
JP2020102606A